When do peers matter?: A cross-country perspective. (December 2016) - Francis, Bill B.; Hasan, Iftekhar; Kostova, Gergana L.
Abstract: We assess the importance of industry peers for a firm's own decision making strategy, using a rich sample of data covering 47 countries and 87 different industries between 1990 and 2011. Following the instrumental variable approach suggested by Leary and Roberts (2014), we find that, similar to U.S. firms, foreign firms do follow their peers when they make financial policy decisions. A standard deviation increase in peer firms' average leverage leads to about 5 percentage point increase in a firm's own leverage. We also find evidence that firms are more likely to follow their peers when investor protection laws including information disclosure and minority shareholder protection are weak, when creditor rights laws are strong, and when equity markets are more developed, suggesting that peers matter the most when firms have the greatest need to learn and to demonstrate their quality. These results hold even when we perform the analysis on a matched sample of firms.